En energieffektiviserad skärgårdstrafik – ur ett ekonomiskt perspektiv - Olausson, Julia; Stücken, Kim (My University, 2017)
Styrsöbolaget traffic in Gothenburg's southern archipelago and the Göta Älv River with smaller passenger vessels. The aim of this work is to get an idea of how much energy two of the ships, Valö and Älvsnabben 4, consumes and what measures that can reduce the energy consumption. This energy concerns the ship's lighting and heating systems as Styrsöbolaget already has a good track of the energy that goes into propulsion. Two experiments were performed, a shore power measurement with a power meter which logged how much kW the ship uses and a measurement of an auxiliary engine to obtain the hourly consumption of diesel. The auxiliary engine measurement was done by cutting off the ship's fuel tank and replaced it with a graduated container where you could read the diesel consumption. The results of the measurements were compiled in various charts and a cost could be calculated, both hourly and annual cost, from both energy production options that could be compared with each other. The results show that there are about twice as expensive in most cases running on an auxiliary engine compared to when shore power is connected. To reduce this energy consumption, you can change the procedures on board to some extent and some technical systems can be added on board. Some routines that can be changed is that you begin to turn off the lights where there are no people, and that the shore power is connected for a longer time. Technical systems that can be installed, is for an example, solar cells or a system that takes care of the waste heat in the exhaust.
Keywords: Farkostteknik; Hållbar utveckling; Transport; Vehicle Engineering; Sustainable Development; Transport